2008
DOI: 10.1086/593017
|View full text |Cite
|
Sign up to set email alerts
|

Early Depletion ofMycobacterium tuberculosis–Specific T Helper 1 Cell Responses after HIV‐1 Infection

Abstract: Background The acid-fast bacillus Mycobacterium tuberculosis (MTB) is often the first manifestation of AIDS in HIV infected patients. This study was conducted to better understand the mechanism underlying MTB-specific pathogenicity early in HIV infection. Methods MTB-specific T Helper 1 (TH1) cells were studied in HIV negative (n=114) and chronically HIV infected (n=68) Tanzanian subjects usinEarly Secreted Antigenic Target 6 (ESAT6) protein or Tuberculin (PPD) by Interferon gamma (IFNγ) ELISPOT and intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 39 publications
9
136
2
3
Order By: Relevance
“…Functional impairment of the mycobacteria-specific CD4 T-cell response in peripheral blood from HIV-1-infected persons has been well described (24,25) and may persist during cART (26). A recent longitudinal study also showed that acute HIV-1 infection induced a rapid depletion of M. tuberculosis-specific responses in persons who remained free of TB symptoms (43).…”
Section: Discussionmentioning
confidence: 99%
“…Functional impairment of the mycobacteria-specific CD4 T-cell response in peripheral blood from HIV-1-infected persons has been well described (24,25) and may persist during cART (26). A recent longitudinal study also showed that acute HIV-1 infection induced a rapid depletion of M. tuberculosis-specific responses in persons who remained free of TB symptoms (43).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that the frequency of IFN-␥-producing CD4 T cells responsive to the highly immunogenic ESAT-6 or CFP-10 peptide or to an ESAT-6/CFP-10 fusion protein exhibited a negative correlation with the total CD4 T cell count in HIV-infected, antiretroviral-naïve subjects, implying that CD4 T cells responsive to these antigens are relatively spared during the progressive depletion of total CD4 T cells by HIV (121). In contrast, another study analyzed the frequency of IFN-␥-secreting cells after stimulation with recombinant ESAT-6 or CFP-10 proteins and reported that a lower proportion of HIV-infected individuals had specific responses above a defined cutoff of responding cells (109). In that cross-sectional study, those authors found no correlation between the number of ESAT-6-or CFP-10-responsive cells and the total CD4 T cell count in HIV-infected or -uninfected subjects.…”
Section: Hiv Effects On Tb Immunity: Evidence For and Against Selectimentioning
confidence: 99%
“…La récupération des réponses T CD4 + est particulière-ment marquée dans le cas du TB-IRIS. Dans la phase d'infection chronique qui précède le traitement antirétroviral, le VIH cible et élimine préférentiellement les lymphocytes T CD4 + spécifiques de Mtb, par comparaison aux T CD4 + spécifiques d'autres pathogènes, comme le CMV [22]. Ce ciblage pourrait s'expliquer par l'état de différenciation des T CD4 + spécifiques de Mtb, qui produisent plus d'interleukine-2 (IL-2) et moins de -chimiokines, telles que MIP-1 (macrophage inflam- 4), par comparaison aux cellules spécifiques de CMV, l'IL-2 favorisant la réplication du VIH et les -chimiokines inhibant cette réplication par l'occupation du corécepteur CCR5 (C-C chemokine receptor 5) [23].…”
Section: Mécanismes Possibles De L'iris Reconstitution Rapide Des Répunclassified